The Competencies of the Supply Chain Management in the System of Economic Security of Russian Enterprises - Tatyana Anatolyevna Snetkova; Pavel Alexandrovich Aletkin; Svetlana Sergeevna Meleshenko (International Journal of Supply Chain Management, 2020)
Abstract— The level of economic security of an entity is heavily influenced by administrative and legal status of Supply chain management. Legal status of Supply chain management determined specifics of his work. Supply chain management belongs to the leaders of the economic-financial and administrative units of the organization. Emphasis on professional competence, labour functions and legal status of Supply chain management in ensuring the economic security of an entity in the light of the introduction in Russian practice of a professional standard "Accountant" is made. The widespread use of the practice of the Russian companies of professional standards, including those related to the procedures of the organization and conduct of audit and control services will organize work on compliance with economic security, develop and implement a system of events. The impact of accounting on the basis of professional standards "Accountant", "Internal Comptroller" and "Internal auditor" and labour competencies and functions on a system of economic security of an entity is examined. In modern conditions the professionalism and qualification of accountants, including Supply chain management, define their importance in providing economic security will allow program implementing a national system for assessing qualifications.